Designing Popular Classes on Viewboard Public Assessment of Lectures Based on YII Framework - Handayani, Indri; Febriyanto, Erick; Jethro, Andrew (Aptisi Transactions On Technopreneurship (ATT), 2019)
The lecture support system in Higher Education has information about student identity in each system, such as profile photos, names, NIM (Student Registration Number) and according to system requirements. An assessment on the public viewboard is an Online Assessment System aimed at improving services at Raharja University. However, in the multiplication flow system still has 3 disadvantages, namely, students do not yet have the facility to see the allocation value between friends in one class in one course to be able to improve the results of lecture grades with classmates and also between classes. In class design Popular writers also do five methods, namely the method of analysis, method of literature review, observation method, design method, and then implemented. With the existence of this study, there are 3 Benefits, namely, students can see the value determined by classmates, can improve the value, and lecturers can ensure the value given must be recognized by students.